Legal responses to placebo-controlled trials in developing countries. Issue 2 (1st October 2016) - Pavone, Ilja Richard
ABSTRACT: The conduct of clinical trials involving placebo in developing countries in the presence of an existing effective treatment triggered an intense debate on the standard of care to be provided to those populations. Charges of exploitation of vulnerable groups and double standards have been raised by several scholars. In response to these concerns, the Declaration of Helsinki (DoH) was revised in 2000, 2008 and 2013, eventually endorsing the golden standard instead of the local standard of care. The European Union (EU) adopted a strategy on the Marketing Authorization of medicinal products tested in third countries, improved with Regulation 536/2014 on clinical trials on medicinal products for human use. Additional rules have been enacted by other international organizations (UNESCO, Council of Europe). The present paper has the aim of analyzing scope and content of existing international and regional standards on placebo.